2019
DOI: 10.3390/nu11122924
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the American Cancer Society Guidelines for Cancer Survivors and Health-Related Quality of Life among Breast Cancer Survivors

Abstract: The development and validation of guidelines for breast cancer survivors are of importance due to the increased survival rate for breast cancer. In this cross-sectional study, we aimed to examine the association between adherence to the American Cancer Society (ACS) guidelines for cancer survivors and health-related quality of life (HRQoL). A total of 618 breast cancer survivors aged 30 to 81 years who had been diagnosed with stage I to III primary breast cancer and had surgery at least a year before enrollmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…ACS guideline adherence was found to have a moderating effect on both the adverse effect of stress on HRQoL and on the buffering effects of spousal support. Numbers of studies reported that adherence to the ACS guideline in the breast cancer patients reduced cancer recurrence and mortality [ 12 , 13 , 25 ]. Interestingly, an association between ACS guideline adherence and the QoL of cancer patients has been reported as well; the higher healthy daily habits scores were related to the higher HRQoL levels [ 7 , 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ACS guideline adherence was found to have a moderating effect on both the adverse effect of stress on HRQoL and on the buffering effects of spousal support. Numbers of studies reported that adherence to the ACS guideline in the breast cancer patients reduced cancer recurrence and mortality [ 12 , 13 , 25 ]. Interestingly, an association between ACS guideline adherence and the QoL of cancer patients has been reported as well; the higher healthy daily habits scores were related to the higher HRQoL levels [ 7 , 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the ACS guideline (2012) was estimated by the following categories: (1) achieving and maintaining a healthy body weight using body mass index, (2) engaging in regular physical activity (MET-hours/week), and (3) following the ACS guidelines for cancer prevention (including achievement of a dietary pattern that is high in vegetables, fruits, whole grains, low in processed and red meat, low alcohol intake, and non-smoking). The detailed scoring was described in a previous study by our group [ 13 ]. The score range of ACS guideline adherence was defined between 3 and 12.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, cancer survivors are advised to follow some diet recommendations from the American Cancer Society (ACS) Guideline on Diet and Physical Activity for Cancer Prevention and the World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) Cancer Prevention (Table 1). Higher diet scores were associated with many aspects, including bodily pain among breast cancer survivors with stage II-III cancer, according to a cross-sectional study that looked at whether adherence to the American Cancer Society (ACS) guidelines was associated with health-related quality of life (HRQoL) among Korean breast cancer survivors [64]. A study of Chinese patients with breast cancer who followed the WCRF/AICR guidelines (BMI, physical activity, and diet) before and after their diagnosis found that following the BMI prescription resulted in reduced pain scores while adherence to dietary recommendations, on the other hand, was not linked to pain scores [65].…”
Section: Impact Of Diet and Nutrition On Pain In Cancer Survivors Through Malnutrition Nutritional Deficiency And Diet Qualitymentioning
confidence: 99%